Role of participatory research on natural resource management: A case of Karnali Watershed Area, Nepal - Kabi Prasad Pokhrel (African Journal of Environmental Economics and Management, 2013)
This paper discusses the development trends of participatory research in Nepal with reference to natural resource management, taking example from Karnali watershed area. The issues discussed in this paper clearly indicate that there is urgent need to promote the participatory action research on environment and development for the proper links between population, development, technological implication and institutional strengths, using a micro level conservation and development model that suits local environments. The author opines that both government organizations and academic institutions have to join hands with an effort to promote the participatory research culture in Karnali watershed area for sustainable natural resource management.